Ecological network analysis of embodied particulate matter 2.5 – A case study of Beijing. (15th December 2016) - Yang, Siyuan; Fath, Brian; Chen, Bin
Highlights: A PM2.5 emission inventory framework on sectoral scale is constructed. The proportion of direct and indirect PM2.5 emissions is 2:1. Sectors related to industry are the dominant controller of embodied emission network. Abstract: Over the past decades, China has been facing severe airborne pollution associated with atmospheric fine particulate matter (PM2.5 ). Much attention has been paid to the physical transport of PM2.5 emissions. However, the embodied emissions, namely the emissions transferred through economic activities, have seldom been investigated. In this paper, embodied emission of PM2.5 from each sector of Beijing is quantified based on input–output analysis (IOA). Forty-two economic sectors from the input–output table are aggregated into fifteen components. Furthermore, the mutual interactions and control relationship within those sectors have been revealed by using ecological network analysis (ENA) to identify the dominant sectors. The results show that, in 2010, 34% of the total PM2.5 emissions, or 59.4 kt PM2.5, were indirect emissions traded through economic sectors within Beijing. According to the results of ENA, we found that "Smelting & Pressing of Metals", "Metal Products" and "Nonmetal Mineral Products" are the top three sectors with the highest control levels while "Agriculture", "Catering Services" and "Residential Services" are the lowest-ranking sectors among the system. The network confirms that sectors related to heavy industry are the dominant sectors driving the embodied PM2.5 emissions in the whole system. Compared to the conventional approaches for tracking PM2.5 emissions, ENA may provide a practical way to reveal the mechanisms of embodied PM2.5 emission flows via socioeconomic activities from a holistic perspective.